2014
DOI: 10.1139/cjfr-2014-0143
|View full text |Cite
|
Sign up to set email alerts
|

An individual-based growth and competition model for coastal redwood forest restoration

Abstract: Thinning treatments to accelerate coastal redwood forest stand development are in wide application, but managers have yet to identify prescriptions that might best promote Sequoia sempervirens (Lamb. ex D. Don) Endl. (redwood) growth. The creation of successful thinning prescriptions would be aided by identifying the underlying mechanisms governing how individual tree growth responds to competitive environments in coastal redwood forests. We created a spatially explicit individualbased model of tree competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Although the best estimates of a given tree's maximum potential growth rate would require a prohibitive degree of knowledge about a particular tree's genetics and various site factors, a number of recent studies have taken advantage of robust, spatially explicit datasets to estimate the potential diameter growth rate (PDGR) of trees in the absence of competition (Canham et al , 2006Uriarte et al 2004;Coates et al 2009;Gomez-Aparicio et al 2011;Das 2012). PDGR is an estimate of the expected mean potential growth rate without competition for a given species at a given set of sites for a given size tree and should, therefore, be a reasonable measure with which to calculate GI.…”
Section: Introductionmentioning
confidence: 99%
“…Although the best estimates of a given tree's maximum potential growth rate would require a prohibitive degree of knowledge about a particular tree's genetics and various site factors, a number of recent studies have taken advantage of robust, spatially explicit datasets to estimate the potential diameter growth rate (PDGR) of trees in the absence of competition (Canham et al , 2006Uriarte et al 2004;Coates et al 2009;Gomez-Aparicio et al 2011;Das 2012). PDGR is an estimate of the expected mean potential growth rate without competition for a given species at a given set of sites for a given size tree and should, therefore, be a reasonable measure with which to calculate GI.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, as diameter growth is expected to increase with tree size until leveling off or even sometimes decreasing for the largest trees [40], and most of the trees observed in this study have small DBH (mean 20 cm). The parameter linking growth to the competition index (β 2 ) is negative ( Table A5), confirming that growth declines with increasing crowding [40,41]. The average temperature of previous year has a negative effect on growth of PICO, QUCH, PILA, CADE and PIPO, but a positive effect on growth of ABMA and QUKE.…”
Section: Pimo Pico Abma Pije Abco Quke Quch Pila Cade Pipomentioning
confidence: 71%
“…To model competition, we used the Heygi index, which is the neighbor's diameter divided by the distance to the targeted tree summed over all neighbors: [40,41,[48][49][50][51]. This competition index was correlated with tree growth in other studies in the same geographic area [40,52,53].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thinning operations accelerate the development of larger diameter redwood trees [73,86,87], promoting old forest structural features beneficial for creation of wildlife habitat [8]. Modeling early redwood stand growth confirms results from empirical thinning studies: thinning can substantially increase growth of remaining trees and accelerate process of stand development [76]. Berrill et al [77] modeled young plantations with and without thinning and found thinning put stands on a more rapid trajectory towards the desired old forest reference condition.…”
Section: Older Redwood Stand Managementmentioning
confidence: 86%